2021
DOI: 10.1101/2021.01.07.425621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular dynamics simulations and functional studies reveal that hBD-2 binds SARS-CoV-2 spike RBD and blocks viral entry into ACE2 expressing cells

Abstract: New approaches to complement vaccination are needed to combat the spread of SARS-CoV-2 and stop COVID-19 related deaths and long-term medical complications. Human beta defensin 2 (hBD-2) is a naturally occurring epithelial cell derived host defense peptide that has antiviral properties. Our comprehensive in-silico studies demonstrate that hBD-2 binds the site on the CoV-2-RBD that docks with the ACE2 receptor. Biophysical and biochemical assays confirm that hBD-2 indeed binds to the CoV-2-receptor binding doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 104 publications
2
26
0
1
Order By: Relevance
“…Additionally, reduced levels of VREs (important in AMP induction (McMahon et al, 2011;Aguilar-Jimenez et al, 2013)) in cells isolated from bronchoalveolar lavage were found in patients infected with CoV-2 than healthy subjects (George et al, 2020). Moreover, the fact that LL-37 (Zhang et al, 2020) and hBD-2 (Zhang L. et al, 2021), both regulated through Vit D 3 , were able to block S protein-expressing pseudovirions from infecting vulnerable human cells supports the notion that healthy levels of Vit D 3 may be important in reducing the risk of acquiring SARS-CoV-2 infection. However, further studies on the direct correlation between Vit D 3 and AMP levels in relation to susceptibility to CoV-2 acquisition are required.…”
Section: Vitamin D Deficiency and Covid-19: A Possible Link With Antimicrobial Peptidesmentioning
confidence: 98%
See 4 more Smart Citations
“…Additionally, reduced levels of VREs (important in AMP induction (McMahon et al, 2011;Aguilar-Jimenez et al, 2013)) in cells isolated from bronchoalveolar lavage were found in patients infected with CoV-2 than healthy subjects (George et al, 2020). Moreover, the fact that LL-37 (Zhang et al, 2020) and hBD-2 (Zhang L. et al, 2021), both regulated through Vit D 3 , were able to block S protein-expressing pseudovirions from infecting vulnerable human cells supports the notion that healthy levels of Vit D 3 may be important in reducing the risk of acquiring SARS-CoV-2 infection. However, further studies on the direct correlation between Vit D 3 and AMP levels in relation to susceptibility to CoV-2 acquisition are required.…”
Section: Vitamin D Deficiency and Covid-19: A Possible Link With Antimicrobial Peptidesmentioning
confidence: 98%
“…Recent in silico molecular docking studies predicted strong binding interactions of LL-37 (Lokhande et al, 2020) and hBD-2 (Zhang L et al, 2021) with the receptor-binding domain (RBD) of SARS-CoV-2, suggesting an RBD blocking potential for these two peptides. Biophysical assays using bio-layer interferometry (BLI) and microscale thermophoresis (MST) supported the in silico findings for LL-37 (Wang C. et al, 2021) and hBD-2 (Zhang L. •Aggregates IAV and enhances neutrophil-mediated clearance [Hartshorn et al (2006), Tecle et al (2007), Doss et al (2009)] •Inhibits IAV replication through the inhibition of protein kinase C (PKC) in infected cells [Salvatore et al (2007)] HD5…”
Section: Antimicrobial Peptides As Viral Binding Inhibitors That Can Block Cov-2 Entrymentioning
confidence: 99%
See 3 more Smart Citations